Comunidade de formigas ao longo de um gradiente altitudinal: Influência do tipo de vegetação e de fatores ambientais e climáticos - Lasmar, Chaim José (2016)
Elevational gradients are ideal for testing ecological theories, species richness patterns and species ranges and its effects upon climatic changes. In this sense, this study evaluated the vegetation type effect on patterns of ant species richness in a tropical elevational gradient. We compared two kinds of approach in an elevational gradient: one sampling only in forest formations type across the gradient and another sampling in two vegetation types constituted by forest and grasslands formations. Besides that, we also evaluated alpha, beta and gamma diversity along elevation, and beta diversity and its main mechanism between elevational bands always correlating them to environmental and climatic factors. It has been found that vegetation type may bias ant species richness‟ patterns. Probably different conditions of those two vegetation types are influencing it. Alpha and gamma diversity followed a species monotonic decline along the gradient. In addition, the beta main mechanism between elevational bands was by the turnover of species. Alpha and gamma were correlated with temperature. Ants might be injured at highlands, wherein low levels of temperature may compromise its foraging and larval development. Therefore, lowlands with its higher levels of temperature might permit more co-occurrence of ant species than highlands. Beta diversity and its main mechanism (turnover) between elevational bands were correlated with temperature. Such climatic factor possibly selects ants that can survivor at low temperatures, acting as a species filter. In this sense, a rapidly change as consequence of global warming might compromise ant fauna of tropical mountains.